2021
DOI: 10.1186/s42492-021-00097-7
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of machine learning techniques on diabetes detection

Abstract: Diabetes mellitus has been an increasing concern owing to its high morbidity, and the average age of individual affected by of individual affected by this disease has now decreased to mid-twenties. Given the high prevalence, it is necessary to address with this problem effectively. Many researchers and doctors have now developed detection techniques based on artificial intelligence to better approach problems that are missed due to human errors. Data mining techniques with algorithms such as - density-based sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Remarkably, there is a rich library of available machine learning methods used for developing models to deal with a specific problem, and it is crucial to select an appropriate ML method to improve the performance of the models ( 4 ). Recent studies indicate that diabetes prediction models developed based on images, electronic health records, or structured data obtained from their societies, using machine learning algorithms such as Decision Tree, Naive Bayes, SVM, ANN, etc., achieve superior performance and demonstrate their potential to be helpful for diabetes screening ( 38 , 39 ). We employed seven ML algorithms for diabetes screening using data from our population-based study in China, including LGBM, ANN, SVM, RF, KNN, CDKNN and LR, which are reported to have good performances in developing predictive models with high accuracy in recent studies ( 40 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, there is a rich library of available machine learning methods used for developing models to deal with a specific problem, and it is crucial to select an appropriate ML method to improve the performance of the models ( 4 ). Recent studies indicate that diabetes prediction models developed based on images, electronic health records, or structured data obtained from their societies, using machine learning algorithms such as Decision Tree, Naive Bayes, SVM, ANN, etc., achieve superior performance and demonstrate their potential to be helpful for diabetes screening ( 38 , 39 ). We employed seven ML algorithms for diabetes screening using data from our population-based study in China, including LGBM, ANN, SVM, RF, KNN, CDKNN and LR, which are reported to have good performances in developing predictive models with high accuracy in recent studies ( 40 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…While [7], [11], studied the utilization of soft computing techniques in diagnosing tropical febrile diseases, and found that ensemble techniques were used more frequently than single machine learning techniques, with Dengue fever being the most studied disease. The other works [7], [10]- [13] study aimed to address the diabetes problem effectively by utilizing arti cial intelligence-based detection techniques, such as density-based spatial clustering [15] of applications with noise and ordering points to identify the cluster structure, machine vision systems, and iridocyclitis for detection of the disease through iris patterns.…”
Section: Ict In Medicinementioning
confidence: 99%
“…Both the above issues assume noticeable importance in the medical domain, e.g., diabetes management. Several techniques have been investigated to discover data-driven glucose forecasting models, ranging from approaches based on regression [ 35 , 36 , 37 , 38 , 39 ] to those that handle the prediction as a classification problem [ 29 , 40 , 41 , 42 ]. These techniques can be classified as explainable or interpretable based on the techniques employed for discovering the learning model.…”
Section: State Of the Artmentioning
confidence: 99%